Non-user benefits emanating from enhanced water flow to the Yala Protected Area Complex - Weligamage, Parakrama; Butcher, W. R.; Blatner, K.A.; Shumway, C.R.; Giordano, Mark (2010)
Water is a multiple use resource. Increasing scarcity and competition from various sectors is an important dimension to be considered in its management. Understanding the value of water to different water uses is, therefore, necessary to assist decision-making in water allocation among sectors. Although water used in agriculture can be valued using production function approaches, such direct valuation methods are not available for the environmental uses of water. This paper uses non-market valuation methods to estimate the economic value of a committed flow through a unique ecosystem, the Yala Protected Area Complex (YPC). The Yala Protected Area Complex is an important wildlife refuge situated in south-eastern Sri Lanka. Its large land extent, undisturbed nature, and abundance and diversity of fauna contribute to its uniqueness. The fact that the YPC is also the most visited national park in Sri Lanka is partially a result of this uniqueness. However, maintenance of the park?s ecosystem depends on the flow of the Menik Ganga. This flow is regulated by the Veheragala Reservoir Project, and there is now discussion of reducing flow into the park by about half of the current level. The proposed plan ensures dry season flow into the YPC and, therefore, has been deemed acceptable. However, there is a possibility that farmers will demand further water releases during the dry season which could in turn endanger the planned downstream water releases. So there is a potential trade-off between environmental and irrigation uses of water. A willingness to pay (WTP) survey was conducted in ten districts in Sri Lanka during the fourth quarter of 2008 to estimate the WTP of the general population of the country towards maintaining this important environmental resource. In the hypothetical market presented, participants were told of the need for financial contributions from the general public to ensure the release of a minimum downstream flow commitment of 50 MCM. Participants were also informed of how this flow would enhance the ecosystem of the YPC. A single bound dichotomous choice contingent valuation approach was used as the elicitation format. Nonobligatory voluntary contributions were solicited towards a trust fund that could be used to ensure release of the required quantity of water downstream during dry months. According to the results of a binary logistic regression, income, age, and religious attachments are important factors affecting the decision to contribute to environmental flow maintenance to the YPC. Sixty-five percent of respondents were willing to pay something to ensure the maintenance of an adequate environmental flow in the YPC. The estimated mean WTP for water releases to enhance the YPC is Sri Lankan Rupees (SLR) 435 per year. Over the requested payment horizon of 10 years, the present value of aggregate WTP from the Sri Lankan population to enhance the ecosystem of the YPC is SLR 12 billion. This quantity greatly surpasses the present value of net benefits from rice farming estimated at SLR 0.64 billion, which would be generated if the same quantity of water was used for irrigation for 10 years (assuming current prices and input intensities). Thus, there is a clear opportunity for national welfare gain by ensuring adequate flow in YPC.